Early Childhood Curiosity and Kindergarten Reading and Math Academic Achievement - Shah, Prachi E. (Pediatr Res, 2018)
BACKGROUND: Although children’s curiosity is thought to be important for early learning, the association of curiosity with early academic achievement has not been tested. We hypothesized that greater curiosity would be associated with greater kindergarten academic achievement in reading and math. METHODS: Sample included 6200 children in the Early Childhood Longitudinal Study, Birth Cohort. Measures at kindergarten included direct assessments of reading and math, and a parent-report behavioral questionnaire from which we derived measures of curiosity and effortful control. Multivariate linear regression examined associations of curiosity with kindergarten reading and math academic achievement, adjusting for effortful control and confounders. We also tested for moderation by effortful control, sex, and socioeconomic status (SES). RESULTS: In adjusted models, greater curiosity was associated with greater kindergarten reading and math academic achievement: b(reading)=0.11, p<.001; b(math)=0.12, p<.001. This association was not moderated by effortful control or sex, but was moderated by SES (p(reading)=.01; p(math)=.005). The association of curiosity with academic achievement was greater for children with low SES (b(reading)=0.18, p<.001; b(math)=0.20, p<.001), versus high SES (b(reading)=0.08, p=.004; b(math)=0.07, p<.001). CONCLUSIONS: Curiosity may be an important, yet under-recognized contributor to academic achievement. Fostering curiosity may optimize academic achievement at kindergarten, especially for children with low SES.